Development of a sensitive microextraction strategy for the accurate determination of tebuconazole and etrimfos by gas chromatography-mass spectrometry - Akarcay, Nur Azize; Chormey, Dotse Selali; Kasa, Nursu Aylin; Zaman, Buse Tugba; Bakirdere, Sezgin (TAYLOR & FRANCIS LTD, 2020)
This study presents the optimisation of a dispersive liquid-liquid microextraction method for the preconcentration of etrimfos and tebuconazole before gas chromatography mass spectrometry (GC-MS) detection. The parameters including extraction and dispersive solvents, salting out effect, and mixing type and period were optimised in order to increase the extraction output of the analytes. Under the optimum extraction conditions, the limit of detection recorded for etrimfos and tebuconazole were found to be 0.88 and 1.3 ng/mL, respectively. The calibration plots developed for both analytes showed good linearity over a wide concentration range. Spiked recovery experiments were used to determine the method's applicability to real samples (tap and wastewater), and appreciable results (89-100%) were obtained for the samples spiked at 10, 20 and 50 ng/mL. Percent relative standard deviations calculated for six replicates of the lowest concentration in the calibration plots were below 7.0% for both analytes, and this established good precision.
Keywords: DLLME; GC-MS; pesticides; etrimfos; tebuconazole; LIQUID-LIQUID MICROEXTRACTION; PESTICIDE-RESIDUES; HEALTH IMPACT; WATER; PRECONCENTRATION; EXTRACTION; Chemistry; Environmental Sciences & Ecology